Effect of Grazing Treatments on Phenotypic and Reproductive Plasticity of Kobresia humilis in Alpine Meadows of the Qinghai-Tibet Plateau - Wang, Lin; Jing, Yuanyuan; Xu, Changlin; Yu, Xiaojun (Frontiers in Environmental Science, 2022)
Plant phenotypic and reproductive plasticity is strongly influenced by long-term grazing activities. It is important to understand the life history of dominant plant species, such as Kobresia humilis of alpine meadow, for the stability and sustainable grazing administration meadow on the Qinghai-Tibetan Plateau (QTP). We compared the effects of different grazing treatments (grazing yak, Y; grazing Tibetan sheep, S; and grazing Tibetan sheep and yak, S+Y) on the reproductive and phenotypic plasticity of K. humilis in an alpine meadows on the northeastern margin of the Qilian Mountains in China. The results showed that different grazing treatments had significantly effects on the K. humilis phenotype and reproductive plasticity. The Y treatment significantly reduced the plant height, crown width and K. humilis biomass, but increased the density, which was 1.27 and 1.53 times higher than that in the S+Y and S treatments, respectively. Further, the S+Y treatment significantly increased the crown width, biomass, and future life expectancy of K. humilis. Whereas the S treatment increased the height of K. humilis significantly, which was 1.57 and 1.10 times higher than that in the Y and S+Y treatments, respectively. Both Y and S treatments significantly increased the sexual reproduction efficacy of K. humilis but reduced the storage efficacy. The storage efficacy at S+Y treatment was highest among these treatments. Further, grazing treatments did not change the resource allocation strategy of K. humilis, while the sexual reproductive efficacy was significantly higher than the vegetative reproduction efficacy. The storage efficacy was significantly higher than the growth efficacy among the different grazing treatments. The increase of Cyperaceae indicates the degradation of Cyperaceae - Poaceae meadows. This study showed that grazing Tibetan sheep is a more sustainable grazing method in cold season pastures of alpine meadows on the QTP.